THE EFFECTIVENESS OF EARLY DETECTION OF KAMTIB DISTURBANCES THROUGH CORRECTIONAL GREETING ACTIVITIES AT RUTAN IIB MENGGALA - Riyantyo, Fadhel; Soge, Markus Marselinus (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research explores the effectiveness of early detection of security disturbances through the Salam Pemasyarakatan program at Rutan IIB Menggala. The study aims to evaluate how this humanistic approach contributes to enhancing communication between staff and inmates, facilitating early intervention to maintain order within the correctional facility. Employing a qualitative research methodology, data was collected through observations and interactions during the implementation of the program. The findings reveal that the program significantly improves staff-inmate relationships, leading to more effective communication and timely identification of potential disturbances, particularly regarding drug circulation and conflicts among inmates. Despite facing challenges such as inconsistent implementation and limited personnel, the Salam Pemasyarakatan program proves essential in fostering a secure environment. This research underscores the importance of integrating humanistic practices in correctional management to enhance security and rehabilitation efforts. Keywords: Early Detection; Correctional Facility; Greeting (Salam Pemasyarakatan)